Biochar production from poultry litter as management approach and effects on plant growth - S. Sikder; J. C. Joardar (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose A lots of poultry litter (PL) is being generated every day from poultry industries and improper management leads to different environmental problems. Production of biochar from PL is a new management strategy of PL which is a nutrient-rich organic amendment for improving soil nutritional status. The experiment was aimed for the production of poultry litter biochar (PLB) from fresh PL to assess the important properties of both PL and PLB, and to observe the effects on plant growth. It also appraised the change of soil properties after PL and PLB application. Methods Poultry litter biochar was produced from fresh PL heated at 300 °C temperature for 10 min in muffle furnace. Poultry litter was applied into the soil at 2.5, 5.0, 7.5 and 10 t ha−1 and PLB was applied at 1, 2, 3 and 4 t ha−1 along with control. Gima kalmi (Ipomoea aquatica) was grown as test plant. To assess the potentiality and residual effect, the same plant was grown consecutively after harvesting first crop. Post-harvest soil analysis was also carried out after harvesting the first crop. Results After pyrolysis pH, EC, organic carbon, available nitrogen, phosphorus, potassium, calcium, total phosphorus, potassium, calcium, magnesium, and iron were increased in PLB. A significant (p < 0.001) increase in plant growth and biomass production was observed and it was higher in PLB-treated soil than that of the PL-treated soil for both first and second crop. Conclusion Poultry litter biochar might be a promising organic fertilizer with high nutrient composition than fresh PL. This also could be an ecofriendly management strategy for sustainable agriculture and long-term productivity.